PERSPEKTIF DESAIN PEMBELAJARAN BAGI GURU - Abdul Hamid (Balai Diklat Keagamaan Banjarmasin, 2020)
Today Perspective ( point of view ) learning design is no longer a strange matter especially in education, both formal education and non formal education. In the world of formal education learning design changes and evolves according to the purpose of education itself. Learning Design can direct all forms of educational activities to achieve its goals and is central to the entire educational process. The formulation of learning design concept is a way to achieve learning objectives, learning design as a way of delivering instructional materials, instructional design as experience in facing learning process, instructional design as summary in planning of education / teaching, instructional design as part of teaching system.While in principle the design of learning should be a determinant in the purpose of education and can choose the content, the process of learning activities to the selection of media as well as learning and assessment tools. Dewasa ini Perspektif ( sudut pandang ) Desain Pembelajaran bukan lagi suatu hal yang asing khususnya di dunia pendidikan, baik pendidikan yang formal maupun pendidikan non formal. Pada dunia pendidikan formal Desain Pembelajaran mengalami perubahan dan berkembang sesuai dengan tujuan dari pendidikan itu sendiri. Desain Pembelajaran dapat mengarahkan segala bentuk aktifitas pendidikan untuk mencapai tujuan-tujuannya serta berkedudukan sentral dalam seluruh proses pendidikan. Rumusan konsep desain pembelajaran adalah cara untuk mencapai tujuan pembelajaran, desain Pembelajaran sebagai cara dalam meyampaikan bahan ajar, desain pembelajaran sebagai pengalaman dalam menghadapi proses belajar, desain pembelajaran sebagai rangkuman dalam merencanakan pendidikan / pengajaran, desain pembelajaran sebagai bagian dalam sistem pengajaran . Sedangkan pada prinsipnya desain pembelajaran harus menjadi penentu dalam tujuan pendidikan dan dapat memilih isi, proses kegiatan pembelajaran sampai ke pemilihan media serta alat pembelajaran dan penilaian.